Biosynthetic pathway and optimal conditions for the production of indole-3-acetic acid by an endophytic fungus, Colletotrichum fructicola CMU-A109 - Numponsak, Tosapon; Kumla, Jaturong; Suwannarach, Nakarin; Matsui, Kenji; Lumyong, Saisamorn (PloS one, 2018)
Endophytic fungi are known to produce indole-3-acetic acid (IAA), which can stimulate plant growth. Twenty-seven isolates of endophytic fungi were isolated from Coffea arabica in northern Thailand. Only one isolate (CMU-A109) produced IAA in vitro. This isolate was identified as Colletotrichum fructicola based on morphological characteristics and molecular phylogenetic analysis of a combined five loci (internal transcribed spacer of ribosomal DNA, actin, β-tubulin 2, chitin synthase and glyceraldehyde-3-phosphate dehydrogenase genes). Identification of a fungal IAA production obtained from indole 3-acetamide (IAM) and tryptophan 2-monooxygenase activity is suggestive of IAM routed IAA biosynthesis. The highest IAA yield (1205.58±151.89 μg/mL) was obtained after 26 days of cultivation in liquid medium supplemented with 8 mg/mL L-tryptophan at 30°C. Moreover, the crude fungal IAA could stimulate coleoptile elongation of maize, rice and rye. This is the first report of IAA production by C. fructicola and its ability to produce IAA was highest when compared with previous reports on IAA produced by fungi.